Recovery and growth of Haplorchis taichui (Trematoda : Heterophyidae) in chicks - Kumchoo K. (2014)
An experimental study was performed to observe the recovery and growth of a minute intestinal fluke, Haplorchis taichui in chicks (Gallus gallus domesticus). Metacercariae of H. taichui were isolated from Jullien's mud carp, Henicorhynchus siamensis, which were collected in the Chiang Mai Province, Thailand. Two hundred metacercariae were orally force-fed to each chick. The intestine of the chicks were examined from day 1 to day 54 post-infection (PI). The incidence of infection was 84.9% (28/33) and the mean intensity was 19.9 (656/33), with the range 0-59. The worm recovery rate was the highest at day 11 PI (29.5%). On day 3 PI, mature adult worms were recovered and 1-200 eggs were observed in the uterus of the worms. The worms grew rapidly in the chicks and the genital organs were fully developed in 14 days. This parasite can survive in chicks up to day 48 PI. It is concluded that they are a suitable definitive host for infection with H. taichui.